Clementis Alexandrini Paedagogus - Clement, of Alexandria, Saint, approximately 150-approximately 215. (Vigiliae Christianae, Supplements, 2002)
The Paedagogus of Clement of Alexandria is almost completely preserved almost completely in a single manuscript, the famous Codex Arethae, copied in the second decade of the tenth century for Arethas, the Archbishop of Caesarea in Cappadocia. The text was copied from an exemplar in poor shape, to the extent that the codex (P) is full of textual corruptions. Most of the first book of the Paedagogus is lost in P. For this part the author had to rely on two old apographs of P. The only extant critical edition of the text was provided by Otto Stählin in 1905. Although in later editions (1936, 1972) corrections and additions were appended, the author was of the opinion that this predecessor was not attentive enough to the meaning of Clement's text and to the textual problems involved. As a result scholars still lack a reliable critical text of the treatise. Marcovich has tried to improve Stählin's remarkable edition by emending the transmitted text wherever it did not make sense, while relying on Clement's sources and on his lexicon and expression employed elsewhere in his opus.